Trabajo colegiado y habilidades blandas en docentes de la Institución Educativa Pública Primaria Secundaria N° 60087 Lucille Gagne Pellerin Río Napo, Loreto 2024 - Tamani López, Leyda (2025)
This research focused on exploring the relationship between collegial work and soft skills in a sample of 60 teachers from the Public Primary Secondary School No. 60087 Lucille Gagne Pellerin, located on the Napo River. Using a quantitative descriptive-correlational approach and a non-experimental design, questionnaires were applied to collect data. The results revealed that teamwork is at an average level and soft skills are at a low level. In addition, a strong positive association was found between both variables, with a Spearman's rho correlation coefficient of 0.853, which indicates a close and significant relationship between them.